2018
DOI: 10.1016/j.bpobgyn.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment of endometriosis-related pain

Abstract: Available medical treatments for symptomatic endometriosis act by inhibiting ovulation, reducing serum oestradiol levels, and suppressing uterine blood flows. For this, several drugs can be used with a similar magnitude of effect, in terms of pain relief, independently of the mechanism of action. Conversely, safety, tolerability, and cost differ. Medications for endometriosis can be categorized into low-cost drugs including oral contraceptives (OCs) and most progestogens, and high-cost drugs including dienoges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 140 publications
1
101
0
6
Order By: Relevance
“…The pathogenesis of endometriosis has not been definitively established, however, the main pathogenic events were an increased expression of estrogen receptors and of a progesterone resistance in endometriotic tissue . Several progestogens administered using different modalities have been treated for endometriosis . LNG‐IUS released 20 μg levonorgestrel every 24 h during a 5‐year period and acted by modifying the hormonal milieu with the goal of inducing atrophy of the ectopic endometrium .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of endometriosis has not been definitively established, however, the main pathogenic events were an increased expression of estrogen receptors and of a progesterone resistance in endometriotic tissue . Several progestogens administered using different modalities have been treated for endometriosis . LNG‐IUS released 20 μg levonorgestrel every 24 h during a 5‐year period and acted by modifying the hormonal milieu with the goal of inducing atrophy of the ectopic endometrium .…”
Section: Discussionmentioning
confidence: 99%
“…26 LNG-IUS released 20 μg levonorgestrel every 24 h during a 5-year period and acted by modifying the hormonal milieu with the goal of inducing atrophy of the ectopic endometrium. 25,26 Thus, LNG- IUS could avoid daily drug intake. LNG-IUS could be one of the available option for postoperative pain relief and preventing recurrence of endomtriosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ratio of ERα to estrogen receptor beta (ERβ) (ERα/ERβ) was significantly higher in red superficial peritoneal lesions compared with black peritoneal lesions and ovarian endometrioma (22). Considering the above-mentioned receptor-endometriotic lesion relationship, Vercellini et al recommended the use of COCs in young patients with early peritoneal lesions in the lesion-based medical approach, and progestins in patients with deep dyspareunia arising from fibrotic nodules with no estrogen receptors (23).…”
Section: Discussionmentioning
confidence: 81%
“…A recent Cochrane review concluded that, based on the limited evidence and high risk of bias, there is insufficient support to judge the effectiveness of COCs alone compared with placebo, or combined with other medical treatments 68 . In addition, the rationale for the use of COCs has been questioned, in that they provide a higher than physiologic dose of estrogen that maintains the existing estrogen-progesterone disequilibrium, and may stimulate the disease 69 . Furthermore, medical contraindications limit the use of COCs in clinical practice 16 .…”
Section: Comparison Of Combined Oral Contraceptives and Dienogestmentioning
confidence: 99%
“…As a consequence, some experts have suggested that progestins be used as first-line medical treatment for endometriosis 16,69 . Some clinical practice guidelines also recommend progestins as first-line therapy 2,13 .…”
Section: Comparison Of Combined Oral Contraceptives and Dienogestmentioning
confidence: 99%